2017
DOI: 10.1080/21580103.2017.1341434
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of soil carbon and nutrient stocks across land use types in a forest region of central Korea

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Characteristics of soil carbon and nutrient stocks across land use types in a forest region of central Korea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Apple trees often require signi cant amounts of calcium to produce high-production fruits, which lead to addition of liming in orchard soil (Vang-Petersen 1980). MP's intensive management practices, including sawdust compost application, pruning, and vegetation control, contributed to a high macronutrient concentration in the soil (Han et al 2017). In contrast, lower calcium levels in PD and QA may result from their acidic pH and natural rooting habits (Bueis et al 2019).…”
Section: Variation In Soil Physical and Chemical Properties Across La...mentioning
confidence: 99%
See 1 more Smart Citation
“…Apple trees often require signi cant amounts of calcium to produce high-production fruits, which lead to addition of liming in orchard soil (Vang-Petersen 1980). MP's intensive management practices, including sawdust compost application, pruning, and vegetation control, contributed to a high macronutrient concentration in the soil (Han et al 2017). In contrast, lower calcium levels in PD and QA may result from their acidic pH and natural rooting habits (Bueis et al 2019).…”
Section: Variation In Soil Physical and Chemical Properties Across La...mentioning
confidence: 99%
“…Such a modi cation can have adverse effects on soil quality and properties. Soil properties and nutrient dynamics are likely to change with land use intensi cation as surface soils are disturbed and replaced by the soil from deeper layers (Han et al 2017;Li et al 2021; Park et al 2021). Moreover, the effects of land use changes on soil quality and properties can also impact root distribution in urban areas through changes in soil pH, organic matter content, and water and nutrient availability (Ramesh et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, tree species in a forest plantation has been reported an important factor related to soil C storage, because the litter inputs in soil may vary depending on tree species in the same plantation (Binkley & Giardina, 1998;Chen & Li, 2003;Framstad et al, 2013;Lukina et al, 2020). Another, authors have been reported the correlation between tree species and C and N stock in the soil (Chen & Li, 2003;Han et al, 2017;Augusto et al, 2002). Besides, soil type and parental material (Angst et al, 2018), type of vegetation (Galicia et al, 2016) and the age of the forest site (Casiano-Domínguez et al, 2018), are important for soil carbon storage.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, estimates of C stocks in forests soil have become relevant at global, national, regional and local scale (Li et al, 2012;Han et al, 2017;Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative evaluation of carbon (C) and nitrogen (N) stocks in forests is important because of the role of C sequestration in mitigating global climate change and sustainable forest productivity. Consequently, estimates of C and N stocks in forests have been made at global, national, regional, landscape, and stand scales [1][2][3][4][5]. The role of C and N stocks in forests is likely to vary on a stand scale because nutrient conversion rates and allocation mechanisms differ between tree species [1,6,7].…”
Section: Introductionmentioning
confidence: 99%